TEST OF BORAX AND FORMALINE ON SNACKS AT MUHAMMADIYAH ELEMENTARY SCHOOL PADANGSIDIMPUAN CITY - Fatma Suryani Harahap; Laila Tussifah Lubis; Heni Mulyani Pohan; Jalilah Azizah; Aisyah Nurmi (Universitas Medan Area, 2022)
According to data from the Food and Drug Supervisory Agency (BPOM), throughout 2012, the incidence of poisoning due to consuming food occupied the highest position, at 66.7%. One of the causes of food poisoning is the presence of food additives such as formalin, borax. At Muhammadiyah Elementary Schools 1, 2 and 3, there are a lot of street food vendors, such as; fried noodles, meatballs, sausages, snacks. This research aims to find out which snacks contain borax and formalin and to find out which snacks are safe and unsafe for children. Sampling used a simple random technique with the assumption that a lot of samples were purchased by children and were thought to contain borax and formalin, so that a sample of 15 snacks were obtained from 6 snack sellers. Then given code seller 1 until 15. In this research, the borax and formalin tests were carried out qualitatively, using test kit. The results of the research show that of the 15 samples of snacks that have been tested, there are no samples that are positive for borax and formalin. It is proven by the absence of color changes that occur in the samples of snacks that have been tested.